Comparative Analysis of Microbial Communities in Each Developmental Stage of Dermacentor nuttalli in Two Regions in Inner Mongolia, China - Li Zhao; Xiao-Nan Dong; Hao Cui; Lian-Yang Sun; Ren Mu; Ming Nie; Jia-Mei Kang; Nan Bu; Yi-Shuai Zhang; Ze-Hao Qi; Zi-Xuan Li; Zi-Long Zhang; et al. (Biology, 2025)
Dermacentor is the most widely distributed tick genus in China. Dermacentor nuttalli, a predominant tick species in Inner Mongolia, can carry and transmit pathogenic microorganisms. Here, D. nuttalli were collected from Ordos (O-D) and Hinggan League (H-D) in the Inner Mongolia. D. nuttalli specimens at different developmental stages were subsequently reared under identical laboratory conditions. Sample processing, nucleic acid extraction, high-throughput sequencing, and microbial community analyses were conducted. Bacterial communities in O-D and H-D were annotated to 8 phyla, 145 genera and 16 phyla, 141 genera, respectively, with Proteobacteria showing the highest relative abundance. Differences in dominant bacterial genera were observed across developmental stages between the two regions. The most abundant bacterial species were Arsenophonus_uncultured_bacterium in O-D and Rickettsia japonica in H-D. Viral communities were annotated to 4 orders, 25 families, 61 genera, and 126 species in O-D and 6 orders, 28 families, 49 genera, 135 species in H-D. Notable difference in the viral genera with >1% abundance were identified at different developmental stages in the two regions. To our knowledge, this is the first study to compare microbial community compositions of D. nuttalli across developmental stages in two Inner Mongolian regions under under identical rearing conditions and to report the presence of R. japonica, Tacheng Tick Virus-2, and bovine viral diarrhea virus in D. nuttalli.